2013
DOI: 10.1007/s11011-013-9438-7
|View full text |Cite
|
Sign up to set email alerts
|

Predominant gray matter volume loss in patients with end-stage renal disease: a voxel-based morphometry study

Abstract: To investigate the pattern of brain volume changes in patients with end-stage renal disease (ESRD) using voxel-based morphometry (VBM) and correlation with clinical and neuropsychological (NP) tests. Fifty seven ESRD patients with no anatomical abnormalities in conventional magnetic resonance imaging [24 patients with abnormal NP scores, 16 male, 39 ± 12 years; 33 patients with normal NP scores, 23 male, 35 ± 9.7 years] and 22 age- and gender-matched healthy controls (14 male, 36 ± 10.1 years) were recruited i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
71
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 29 publications
11
71
4
Order By: Relevance
“…Authors of these studies did not investigate the effect of the specific dialysis modality on spontaneous brain activity in patients with ESRD, because they included patients undergoing hemodialysis and PD and those not undergoing dialysis. In addition, most previous studies have been focused on abnormal gray and white brain matter structures (16,(22)(23)(24)(25)(26). Several studies (2,7,8) included patients with ESRD undergoing hemodialysis and PD, which can have a confounding effect on the study results.…”
Section: Discussionmentioning
confidence: 99%
“…Authors of these studies did not investigate the effect of the specific dialysis modality on spontaneous brain activity in patients with ESRD, because they included patients undergoing hemodialysis and PD and those not undergoing dialysis. In addition, most previous studies have been focused on abnormal gray and white brain matter structures (16,(22)(23)(24)(25)(26). Several studies (2,7,8) included patients with ESRD undergoing hemodialysis and PD, which can have a confounding effect on the study results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some brain regions showed increased FCD in patients with ESRD (including temporal lobe, caudate, and orbitofrontal cortex), which might be attributed to brain functional plasticity or compensation. This finding was partially supported by the voxel-based morphometry study (Zhang et al 2013), in which increased gray matter volume in the right caudate in patients with ESRD was found. However, the exact functional relevance of the increased FCDs in these areas remains unclear.…”
Section: Discussionmentioning
confidence: 60%
“…One positron emission tomography study (Kanai et al 2001) claimed that cerebral oxygen metabolism of cerebral cortex, especially in frontal lobe, decreased dramatically in patients with chronic kidney disease. Zhang et al (Zhang et al 2013) found diffused gray matter volume loss (fontal, occipital, parietal and temporal cortex) in patients with ESRD by using a voxel-based morphometry method. Besides, the serum creatinine showed negative correlation with long-range FCD in bilateral middle frontal gyri and inferior frontal gyri.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations